The Swedish experiment : the COVID-19 response and its controversies / Yohann Aucante. - Aucante, Yohann (Bristol University Press, 2022)
This short book explores Sweden's response to the global pandemic and the wave of controversies it triggered. It helps to makes sense of the response by defining 'a Swedish model' that incorporates the country's value system and offers a case study for understanding the ways in which different national approaches to the pandemic have been compared.